Contactless hearing aid designed for infants - Kulesza, M.; Kostek, B.; Dalka, P.; Czyżewski, A. (Archives of Acoustics, 2006)
It is a well known fact that language development through home intervention for a hearing-impaired infant should start in the early months of a newborn baby's life. The aim of this paper is to present a concept of a contactless digital hearing aid designed especially for infants. In contrast to all typical wearable hearing aid solutions (ITC, ITE, BTE), the proposed device is mounted in the infant's bed with any parts of its set-up contacting the infant's body. A processed speech signal is emitted by low-power loudspeakers placed near the infant's head. The hearing aid architecture employs a digital signal processor based on Texas Instruments technology. Since one of the main problems is the acoustic feedback between the microphone and the loudspeakers, the methods of its elimination are also briefly reviewed in this article. The first of the discussed methods employs an adaptive algorithm, the second alters the frequency response of the entire instrumentation through the use of notch filter banks, and the third incorporates a microphone array and beam-forming techniques. The paper also includes descriptions of some algorithmic solutions engineered by the authors in purpose to eliminate acoustic feedbacks. All the conclusions introduced in this article have been derived based on the simulations of an experimental contactless hearing aid set-up.